Formulation and Evaluation of Terbinafine HCL loaded Nanoparticles for Transungual delivery of drug in Fungal infection - Shikha, Rashmi; Bisht, Dheeraj; Bhardwaj, Manoj; Bisht, Manoj (Journal of Neonatal Surgery, 2025)
In this review we mainly concern about the transungual delivery of drug to treat nail infection which is caused by the infection of a fungus. Transungual drug delivery is regarded as a very desirable treatment for various diseases in nail treatment due to its localized effects, which promote adherence while causing less unfavorable systemic effects. The nail is one of the toughest portions of the human body, and the nail plate presents a challenging barrier for drugs moiety to pass through . Topical medication delivery treatment is useful for treating numerous nail problems since it has localized effects, resulting in less systemic side effects and a better outcome. As compare to oral drug delivery the transungual delivery of drug is more effective it act on targeted site, increase the penetration, improve bio-availability and show rapid action. So for the transungual delivery of a drug there are many formulations such as gel, cream, patches, lotion, and nail lacquer etc.As compare to oral drug delivery the transungual delivery is viscous preparation used as a cosmetic items or to decor our nail of finger and toes. It is more stable formulation for longer use. On the basis of above conclusion nail lacquer is used in transungul drug delivery with addition of nanoparticle (drug loaded) and as cosmetic item to enhance beauty of the nail. The recent advancement on delivery of drug through nail system has lead to the development of anti-fungal nail lacquer.